Association between serum estradiol levels prior to progesterone administration in artificial frozen–thawed blastocyst transfer cycles and live birth rate: a retrospective study. (27th June 2021) - Zhou, R; Zhang, X; Huang, L; Zhu, X; Dong, M; Liu, W; Wang, S; Liu, F
Abstract : Objective: To study whether serum estradiol (E2) levels prior to progesterone administration in the artificial endometrial preparation (AEP) of frozen–thawed blastocyst transfer affect the live birth rate. Design: Retrospective cohort study. Setting: Tertiary‐care academic medical centre. Population: A total of 3857 frozen–thawed blastocyst transfer cycles were divided into three groups: <200 pg/ml ( n  = 1676); 200–399 pg/ml ( n  = 1296); and ≥400 pg/ml ( n  = 885), based on the 25th (182.3 pg/ml) and 75th percentile (390.2 pg/ml) of serum E2 level prior to progesterone administration. Methods: Univariable and multivariable logistic regression analysis was performed. Main outcome measures: The primary outcome of the study was the live birth rate and the secondary outcomes included clinical pregnancy rate, pregnancy loss rate, neonatal birthweight, Z ‐score, and small for gestational age (SGA). Results: Compared with the reference group, accounting for major covariates, the live birth rate significantly decreased in the '≥400 pg/ml' group (adjusted OR 0.71, 95% CI 0.59–0.85). Compared with the reference group, there was an association between the E2 level in the '≥400 pg/ml' group and a decrease in the clinical pregnancy rate (adjusted OR 0.74, 95% CI 0.61–0.89). Compared with the reference group, the pregnancy loss rate significantly increased in the '≥400 pg/ml' group (adjusted OR 1.45, 95% CI 1.08–1.93). The E2 levels did not affect neonatal birthweight, Z ‐score, and SGA among singletons. Conclusions: High serum E2 levels prior to progesterone administration in AEP are associated with a decreased live birth rate after frozen–thawed blastocyst transfer. Tweetable abstract: High serum E2 levels prior to progesterone administration in artificial FET are associated with a decreased live birth rate after frozen–thawed blastocyst transfer. Tweetable abstract: High serum E2 levels prior to progesterone administration in artificial FET are associated with a decreased live birth rate after frozen–thawed blastocyst transfer.